2010
DOI: 10.1002/lsm.20926
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of the excimer laser assisted non‐occlusive anastomosis (ELANA) flap retrieval rate

Abstract: The flap retrieval of the ELANA anastomosis technique can be optimized to 100% by setting the laser energy at 15 mJ. However, safety studies are necessary before clinical application. A second lasing episode of 10 mJ is a good alternative to increase the flap retrieval. Moreover, the surgeon should be trained to apply not more than 0.2 N on the catheter.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…Laser technology is promising, especially with newer devices that burn a perfect circle through the wall of branch vessels using suction to hold onto the flap, preventing it from floating downstream; this technique is currently used for cerebral revascularization in neurosurgical procedures. 22,23 …”
Section: Discussionmentioning
confidence: 98%
“…Laser technology is promising, especially with newer devices that burn a perfect circle through the wall of branch vessels using suction to hold onto the flap, preventing it from floating downstream; this technique is currently used for cerebral revascularization in neurosurgical procedures. 22,23 …”
Section: Discussionmentioning
confidence: 98%
“…The objective of this study was to assess the effect of increasing the laser energy on the vessel wall of the recipient artery of the ELANA anastomosis in order to determine whether it is safe to apply the optimized laser settings as suggested by van Doormaal et al 8 in the clinics.…”
Section: Discussionmentioning
confidence: 99%
“…To remove all ambiguity, the number of flaps that are not retrieved should be kept as low as possible. A recent study by van Doormaal et al has shown that the flap retrieval rate can be optimized by (1) increasing the laser energy from 10 to 13 mJ, or 15 mJ (2) by lasing with two laser episodes and (3) by training the surgeon to apply no more than 0.2 N on the catheter 8. Hereby, one laser episode would be sufficient if the energy could be increased to 15 or 18 mJ.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the cerebral bypass operation has experienced a renewed awareness and recent papers indicate the need for technological innovation of this procedure [4,8,10,11,17,18]. Furthermore, cyanoacrylates have been evaluated in the last decades as potential tissue adhesive for biomedical and surgical purposes [8,13].…”
Section: Discussionmentioning
confidence: 99%
“…The further development of the ELANA technique with a view to reducing the number of microsutures, increasing the flap retrieval rate, and minimizing the time of the procedure may be helpful in the advance of a faster and secure minimally invasive bypass technique as shown recently [8,10,11]. …”
Section: Introductionmentioning
confidence: 99%